X-ray shielding composition and method for producing the X-ray shielding composition
A tungsten-bismuth-based X-ray shielding composition with a specific volume ratio addresses the challenge of achieving high shielding and processability, ensuring uniform dispersion and reduced CO2 emissions.
Patent Information
- Application Number
- JP2020213941
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-12-23
AI Technical Summary
Existing X-ray shielding compositions face challenges in achieving both high X-ray shielding properties and good roll processability, particularly when using tungsten due to its high specific gravity and difficulty in processing, leading to issues like bagging and sticking during kneading with rubber materials.
A composition comprising a first shielding material (tungsten or tungsten compounds) and a second shielding material (bismuth, molybdenum, barium, zirconium, tantalum, niobium, or their compounds) is formulated, with a volume ratio of 30-70% and 0.5:9.5 to 8:2, ensuring uniform dispersion and reducing CO2 emissions.
The composition achieves uniform dispersion of shielding materials, maintaining desired X-ray shielding properties equivalent to lead while improving roll processability and reducing environmental impact.
Smart Images

Figure 0007616880000003 
Figure 0007616880000004 
Figure 0007616880000005
Abstract
Description
[Technical field]
[0001] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The embodiments disclosed herein and in the drawings relate to x-ray shielding compositions and methods of making x-ray shielding compositions. [Background technology]
[0002] Traditionally, lead has been widely used as a material for shielding X-rays (X-ray shielding material). Although lead is exempt from the RoHS (Restriction of the use of certain Hazardous Substances in electrical and electronic equipment) Directive when used for X-ray shielding, it is subject to the RoHS Directive in terms of environmental toxicity for other uses. For this reason, there is a tendency to refrain from using lead as an X-ray shielding material, and various X-ray shielding compositions containing X-ray shielding materials that replace lead have been proposed.
[0003] An example of a material that can replace lead is tungsten, and an X-ray shielding composition is known in which powdered tungsten is mixed with rubber. Tungsten has high X-ray shielding properties, but is difficult to process into powder because of its large specific gravity and being a difficult-to-cut material, and emits a lot of CO2 during smelting and refining. Other X-ray shielding materials include bismuth, molybdenum, barium, zirconium, tantalum, niobium, etc. These are easier to process into powder than tungsten and emit less CO2 during smelting and refining, but have low X-ray shielding properties.
[0004] On the other hand, when the X-ray shielding property of tungsten and the processability of other X-ray shielding materials are used complementarily to produce an X-ray shielding composition mixed with a rubber material, a problem occurs with roll processability using a roll mixer (mixing roll). Specifically, when mixing tungsten and other X-ray shielding materials with a rubber material, a phenomenon in which the rubber material does not wind around the roll and sags (bagging) or the rubber material sticks to the roll may occur. When such a phenomenon occurs, both X-ray shielding materials are not uniformly dispersed in the X-ray shielding composition, and the desired X-ray shielding property (for example, equal to or higher than that of lead) cannot be obtained. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2004-531730 [Patent Document 2] JP 2001-083288 A Summary of the Invention [Problem to be solved by the invention]
[0006] One of the problems to be solved by the embodiments disclosed in this specification and the drawings is to provide an X-ray shielding composition that is excellent in terms of both X-ray shielding property and roll processability. However, the problems to be solved by the embodiments disclosed in this specification and the drawings are not limited to the above problem. Problems corresponding to the effects of each configuration shown in the embodiments described later can also be positioned as other problems. [Means for solving the problem]
[0007] The X-ray shielding composition includes a rubber material, and includes a first shielding material and a second shielding material. The first shielding material is mixed with the rubber material and includes at least one of tungsten and a tungsten compound. The second shielding material is mixed with the rubber material and includes at least one of bismuth, a bismuth compound, molybdenum, a molybdenum compound, barium, a barium compound, zirconium, a zirconium compound, tantalum, a tantalum compound, niobium, and a niobium compound. The ratio of the X-ray shielding material composed of the first shielding material and the second shielding material to the X-ray shielding composition is 30 volume % or more and 70 volume % or less, and the volume ratio of the first shielding material to the second shielding material is within a range of 0.5:9.5 to 8:2. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a diagram for explaining the linear absorption coefficient of a single material. [Diagram 2] FIG. 2 is a diagram for explaining the linear absorption coefficient when tungsten and bismuth are mixed. [Diagram 3] FIG. 3 is a diagram for explaining the linear absorption coefficient when tungsten and bismuth trioxide are mixed. [Figure 4] FIG. 4 is a diagram for explaining processability by a roll mixer. [Diagram 5] FIG. 5 is a diagram for explaining the relationship between the volume ratio of tungsten to bismuth or bismuth trioxide and the material density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the X-ray shielding composition according to the embodiment and the manufacturing method of the X-ray shielding composition will be described with reference to the drawings. Note that the embodiment is not limited to the following embodiment. In addition, the contents described in one embodiment can be similarly applied to other embodiments in principle.
[0010] (Embodiment) The X-ray shielding composition according to the embodiment includes a rubber material and an X-ray shielding material. The X-ray shielding material has a first shielding material and a second shielding material. The X-ray shielding composition is provided in various X-ray diagnostic devices, such as a CT (Computed Tomography) device, a general X-ray diagnostic device, an X-ray fluoroscopy device, a mammography device, and an X-ray cart. Specifically, the X-ray shielding composition is applied to an X-ray aperture blade (collimator) that forms an X-ray irradiation field. The X-ray shielding composition may also be applied to the housing of various X-ray diagnostic devices, the ceiling, floor, and wall of an X-ray examination room, and protective clothing worn by X-ray technicians. The shape, size, and application are not limited to the present embodiment.
[0011] The rubber material is preferably one that has high resistance to X-rays, such as ethylene propylene diene rubber (EPDM) or ethylene propylene rubber (EPR).
[0012] The first shielding material is a material that blocks X-rays, and contains at least one of tungsten and a tungsten compound. The first shielding material has a higher X-ray shielding property than the second shielding material. The first shielding material is processed into a powder form. The first shielding material has a higher specific gravity than the second shielding material, and is a difficult-to-cut material, so it is difficult to process into powder, and emits more CO2 during smelting and refining than the second shielding material.
[0013] On the other hand, the second shielding material is a material that shields against X-rays, and contains at least one of bismuth, bismuth compounds, molybdenum, molybdenum compounds, barium, barium compounds, zirconium, zirconium compounds, tantalum, tantalum compounds, niobium, and niobium compounds. The second shielding material is processed into a powder form. Since the second shielding material is a free-cutting material (a material that is difficult to cut), it is easier to process into powder than the first shielding material, and the amount of CO2 emitted during smelting and refining is less than that of the first shielding material.
[0014] The X-ray shielding composition utilizes the X-ray shielding property of the first shielding material and the processability of the second shielding material in a complementary manner. In addition, the ratio of the X-ray shielding material to the X-ray shielding composition and the volume ratio of the first shielding material to the second shielding material are determined so that problems in roll processability using a roll mixer (mixing roll) do not occur when the X-ray shielding composition is mixed with a rubber material.
[0015] The ratio of the X-ray shielding material to the X-ray shielding composition is preferably 40 volume % or more and 60 volume % or less, but may be within the range of 30 volume % or more and 70 volume % or less. The volume ratio of the first shielding material to the second shielding material is preferably 3:7 to 8:2, but may be 0.5:9.5 to 8:2.
[0016] The X-ray shielding composition thus configured can suppress the occurrence of a phenomenon in which the rubber material is no longer wound around a roll and sags (bagging) or the rubber material sticks to the roll when the X-ray shielding material is mixed with the rubber material. This allows the first shielding material and the second shielding material to be uniformly dispersed in the X-ray shielding composition, and a desired X-ray shielding property (for example, equal to or greater than that of lead) can be obtained. Furthermore, the X-ray shielding composition can suppress CO2 emissions by using the second shielding material, compared to the case in which only the first shielding material is mixed with the rubber material.
[0017] The linear absorption coefficient of a single material will be described with reference to FIG. 1. FIG. 1 is a diagram for explaining the linear absorption coefficient of a single material. FIG. 1 shows the linear absorption coefficients (theoretical values) of tungsten (W), bismuth (Bi), bismuth trioxide (Bi2O3), and lead (Pb). In FIG. 1, the horizontal axis corresponds to X-ray energy [keV], and the vertical axis corresponds to the linear absorption coefficient [cm -1 Bismuth trioxide is an example of bismuth oxide and bismuth compounds. The linear absorption coefficient is one of the parameters that indicate X-ray shielding properties.
[0018] As shown in Figure 1, tungsten, bismuth, and bismuth trioxide all have linear absorption coefficients closer to that of lead compared to other materials. Specifically, the linear absorption coefficient of tungsten is higher than that of lead, and it has sufficient X-ray shielding effect as a substitute for lead. In addition, the linear absorption coefficients of bismuth and bismuth trioxide are lower than that of lead, and they have inferior X-ray shielding effect compared to lead.
[0019] The linear absorption coefficient when the first shielding material and the second shielding material are mixed will be described with reference to Figs. 2 and 3. Fig. 2 is a diagram for explaining the linear absorption coefficient when tungsten and bismuth are mixed. Fig. 2 shows the linear absorption coefficient (theoretical value) when tungsten (W) and bismuth (Bi) are mixed at the volume ratio shown in the legend. Fig. 3 is a diagram for explaining the linear absorption coefficient when tungsten and bismuth trioxide are mixed. Fig. 3 shows the linear absorption coefficient (theoretical value) when tungsten (W) and bismuth trioxide (Bi2O3) are mixed at the volume ratio shown in the legend. In Figs. 2 and 3, the horizontal axis corresponds to X-ray energy [keV], and the vertical axis corresponds to the linear absorption coefficient [cm -1 ] corresponds to.
[0020] As shown in Figure 2, when the volume ratio of tungsten to bismuth is 2:8, a shielding effect equivalent to that of lead is obtained. In other words, when the volume ratio of tungsten to bismuth is 2:8 to 9:1, a shielding effect equivalent to or greater than that of lead is obtained. In other words, by mixing tungsten and bismuth so that the volume ratio is 2:8 to 9:1, it is possible to reduce the tungsten content while obtaining a shielding effect equivalent to or greater than that of lead.
[0021] As shown in Figure 3, when the volume ratio of tungsten to bismuth trioxide is 3:7, a shielding effect equivalent to that of lead is obtained. In other words, when the volume ratio of tungsten to bismuth trioxide is 3:7 to 9:1, a shielding effect equivalent to or greater than that of lead is obtained. In other words, by mixing tungsten and bismuth trioxide so that the volume ratio is 3:7 to 9:1, it is possible to reduce the tungsten content while obtaining a shielding effect equivalent to or greater than that of lead.
[0022] (Manufacturing method) For example, the X-ray shielding composition is produced as follows. Materials such as X-ray shielding materials, reinforcing materials, processing aids, plasticizers, and softeners are kneaded with rubber material in an internal mixer. As the internal mixer, a kneader, a Banbury mixer, an intermix mixer, or the like, which is usually used for kneading rubber, can be used. After kneading with the internal mixer, materials involved in the crosslinking reaction, such as crosslinking agents and crosslinking assistants, are kneaded using a roll kneader (mixing roll). Materials such as crosslinking agents and crosslinking assistants react to heat, so it is preferable to use a mixing roll with excellent cooling properties. The rubber material kneaded with the mixing roll is rolled to a thickness that matches the molding die of the shielding sheet as a preform to form an unvulcanized rubber sheet. The unvulcanized rubber sheet is placed in a die and crosslinked into a sheet by hot press molding to obtain a shielding sheet.
[0023] With reference to FIG. 4, the processability using a roll mixer will be described. FIG. 4 shows the relationship between the volume ratio of tungsten and bismuth trioxide and the processability. Specifically, tungsten and bismuth trioxide were mixed so that the volume ratio was 10:0 to 0:10, and the processability was evaluated at each volume ratio. The roll mixer (mixing roll) is a two-roll mixer equipped with two rolls arranged in parallel. The roll mixer is a device that rotates two rolls in opposite directions to each other, and mixes and processes the material while winding it around the rolls.
[0024] As shown in Figure 4, when the volume ratio of tungsten to bismuth trioxide was 8:2 to 10:0, roll processability was poor. Specifically, when mixed at this volume ratio, bagging occurred during mixing, as shown in the balloon on the left of Figure 4, and mixing and homogenization did not progress, resulting in poor processability. Mild bagging can be dealt with by pulling the sagging rubber, etc. Tungsten has a high specific gravity, so when the volume ratio of tungsten becomes high, the rubber itself becomes heavy and is likely to peel off from the roll due to gravity.
[0025] Moreover, when the volume ratio of tungsten to bismuth trioxide was 0:10 to 0.5:9.5, the processability was poor. Specifically, when mixed at this volume ratio, as illustrated in the right balloon of FIG. 4, the material excessively stuck to the roll during kneading, and homogenization did not proceed, resulting in a decrease in processability. When tungsten and other X-ray shielding materials are mixed and mixed with rubber, bismuth trioxide is mixed to compensate for the reduction in the amount of tungsten mixed. However, since bismuth trioxide has a smaller specific gravity than tungsten, the volume ratio of the X-ray shielding material to the X-ray shielding composition is larger than when only tungsten is mixed with the rubber material. Therefore, the strength of the rubber of the X-ray shielding composition is lost during roll kneading, and a phenomenon of sticking to the roll may occur.
[0026] In contrast, when the volume ratio of tungsten to bismuth trioxide was within the range of 0.5:9.5 to 8:2, the workability was good. Specifically, when mixed at this volume ratio, as exemplified by the central bubble in Fig. 4, bagging and roll sticking did not occur, and the material was homogenized between the two rolls, resulting in good workability. Furthermore, when the volume ratio of tungsten to bismuth trioxide was within the range of 1:9 to 8:2, the workability was even better.
[0027] In this way, by mixing tungsten and bismuth trioxide, aggregation during kneading can be prevented and good processability can be maintained. That is, the first shielding material and the second shielding material are mixed at a volume ratio that does not cause bagging or roll sticking.
[0028] The relationship between the volume ratio of tungsten to bismuth or bismuth trioxide and the material density will be described with reference to FIG. 5. FIG. 5 is a diagram for explaining the relationship between the volume ratio of tungsten to bismuth or bismuth trioxide and the material density. FIG. 5 shows the material density value at each volume ratio. In FIG. 5, the vertical axis corresponds to the volume ratio of tungsten to bismuth or bismuth trioxide, and the density [g / cm 3 ] corresponds to.
[0029] As shown in Fig. 5, it was confirmed that when the volume ratio of tungsten to bismuth is about 2:8, the density is equivalent to that of lead. Also, it was confirmed that when the volume ratio of tungsten to bismuth trioxide is about 3:7, the density is equivalent to that of lead. When applied as a substitute material for lead, the X-ray shielding composition according to this embodiment is preferably mixed at a volume ratio that results in a density equivalent to that of lead.
[0030] As described above, the X-ray shielding composition according to this embodiment is an X-ray shielding composition in which a first shielding material, a second shielding material, and a rubber material are kneaded. Both the first shielding material and the second shielding material are composed of materials having X-ray shielding properties. In addition, the first shielding material and the second shielding material are kneaded at a volume ratio set so as to maintain processability by a roll kneader. The X-ray shielding composition according to this embodiment has good processability in the manufacturing process.
[0031] For example, in the X-ray shielding composition according to the present embodiment, the volume ratio of the first shielding material to the second shielding material is set so as to suppress bagging and sticking during kneading, and therefore the X-ray shielding composition according to the present embodiment can prevent bagging and sticking to rolls during kneading and maintain good processability.
[0032] Next, the ratio of the X-ray shielding material composed of the first shielding material and the second shielding material to the X-ray shielding composition is 30% by volume or more and 70% by volume or less. This allows both an X-ray shielding rate equal to or higher than that of lead and roll processability to be achieved. If the ratio is less than 30% by volume, it is difficult to obtain a shielding rate equal to that of lead. If the ratio is 70% by volume or more, particles of tungsten or bismuth (or bismuth trioxide) may remain on the surface of the material, which impairs the effect of the rubber material as a binder. Therefore, holes may be formed in the unvulcanized rubber sheet during kneading, which may cause quality problems. In other words, the ratio of the X-ray shielding material composed of the first shielding material and the second shielding material to the X-ray shielding composition is preferably 30% by volume or more and 70% by volume or less. Furthermore, it is preferably 40% by volume or more and 60% by volume or less. If it is 40% by volume or more, the amount of tungsten mixed can be further reduced. If this ratio is less than 60% by volume, the molding process becomes even better.
[0033] Moreover, the second shielding material is more preferably bismuth trioxide. Bismuth trioxide is less likely to aggregate and has better dispersibility than other X-ray shielding materials. Even with other X-ray shielding materials, poor dispersion can be removed by passing the material through a screen mesh or the like, but this increases the number of steps.
[0034] The X-ray shielding composition contains a reinforcing filler in an amount of 0.5% by volume or more and less than 2.0% by volume. Any known reinforcing filler, such as carbon black or silica, can be used as the reinforcing filler. This makes it possible to reinforce the material while maintaining its workability. If the ratio is less than 0.5% by volume, a sufficient reinforcing effect cannot be obtained. If the ratio is more than 2.0% by volume, the X-ray shielding material and other additives cannot be added sufficiently, which may result in limitations on the blending.
[0035] The ratio of the rubber material to the X-ray shielding composition is 20% by volume or more and less than 50% by volume. This can reduce air defects during crosslinking of the sheet. If the ratio is less than 20% by volume, air defects may occur. The air defects and moisture contained in the unvulcanized rubber sheet are compressed at high temperatures during crosslinking of the sheet (during hot press molding). When hot press molding is completed and the mold is opened, the compressed air defects expand, and the moisture becomes water vapor, which significantly increases the volume, resulting in a phenomenon in which the sheet becomes blistered. This phenomenon is believed to occur because, when the ratio of the rubber material to the X-ray shielding composition decreases, the number of crosslinking points of the rubber material decreases, making it impossible to suppress the expanding air and water vapor.
[0036] The occurrence of air defects can be prevented, for example, by not opening the mold at high temperature, but by opening the mold after cooling. However, the increase in the number of manufacturing steps may result in a longer cycle time. Also, if this ratio is 50% by volume or more, there is less room to add other compounding agents such as crosslinking agents. In other words, the ratio of the rubber material to the X-ray shielding composition is preferably 20% by volume or more and less than 50% by volume.
[0037] In addition, since tungsten is the first shielding material, the amount of energy required for smelting and refining the material is large, which leads to a problem of large carbon dioxide (CO2) emissions. In the X-ray shielding composition according to this embodiment, the first shielding material is not used alone but is used in combination with the second shielding material, so that the amount of carbon dioxide emissions during production can be reduced compared to when the first shielding material is used alone.
[0038] In addition, tungsten is known to have a high unit price compared to other materials. In the X-ray shielding composition according to the present embodiment, the first shielding material is not used alone but is used in a mixture with the second shielding material, so that the cost (monetary cost) can be reduced compared to the case where the first shielding material is used alone.
[0039] Although several embodiments have been described, these embodiments are presented by way of example and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, replacements, changes, and combinations of embodiments can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, as well as in the invention described in the claims and the equivalent scope thereof.
[0040] (Example) Examples are shown below to specifically explain the embodiments, but the embodiments are not limited to the following examples.
[0041] <Materials of the X-ray shielding composition> The materials of the X-ray shielding composition used in the examples are shown below. The blending amounts (parts by mass) of each material in each example and comparative example are as shown in Table 1. · Rubber material: EPDM Esprene 505A (manufactured by Sumitomo Rubber Industries, Ltd.) · X-ray shielding material: Tungsten W-4KD (manufactured by Nippon Shin Metals Co., Ltd.) Tungsten carbide WC-15 (manufactured by Nippon Shin Metals Co., Ltd.) Bismuth oxide FP (manufactured by Nippon Chemical Industry Co., Ltd.) Bismuth fine particles (Mitsui Mining & Smelting Co., Ltd.) · Reinforcing filler: Carbon black Asahi #35 (manufactured by Asahi Carbon Co., Ltd.) · Crosslinking agent: Parkmill D-40 (manufactured by NOF Corporation) · Crosslinking aid: Tike M-60 (manufactured by Mitsubishi Chemical Corporation) · Other compounding agents Processing aid: Stearic acid Camellia (manufactured by NOF Corporation) Antioxidant: Nocrack 6C (manufactured by Ouchi Shinko Chemical Industrial Co., Ltd.) Antioxidant: Nocrack MB (manufactured by Ouchi Shinko Chemical Industrial Co., Ltd.) Softening agent: Diana Process PW-90 (manufactured by Idemitsu Kosan Co., Ltd.)
[0042] (Example 1) <Production of Rubber Composition> The components shown in Table 1 were kneaded using a 7L kneader and a 12-inch mixing roll to obtain a rubber composition. Specifically, the rubber material was charged into the 7L kneader and masticated for 1 minute at a rotation speed of 30 rpm, after which each component except the crosslinking agent and crosslinking aid was charged and kneaded for 20 minutes at the same rotation speed, and the rubber mixture was discharged. The filling rate in the mixing tank of the 7L kneader was adjusted to 60%.
[0043] Next, the crosslinking agent and the crosslinking agent were kneaded for 15 minutes using a 12-inch mixing roll with a roll gap set to 5.0 mm and a rotation speed of front roll: 15 rpm / rear roll: 17 rpm to obtain each rubber composition. Each obtained rubber composition was rolled to a thickness of 3.0 mm using the roll to obtain an unvulcanized rubber sheet.
[0044] <Molding / Crosslinking> The unvulcanized rubber sheet obtained above was cut into a size of 135 mm length × 135 mm width, and placed in a mold of 150 mm length × 150 mm width × 2.0 mm depth, and heated at 180°C for 15 minutes under a pressure of 20 MPa using a heat press. After demolding, burrs were removed to obtain an X-ray shielding composition.
[0045] <Evaluation> ·Dispersibility The unvulcanized rubber sheet obtained in the production of the rubber composition was rolled to a thickness of 0.3 mm, and the surface of an area of 150 mm x 150 mm was visually observed. The number of aggregates with a maximum length of 500 μm or more was counted and the dispersibility was evaluated as follows. The evaluation results are shown in Table 2. ◎: No aggregates ○: 1 to 5 aggregates ×: 6 or more aggregates
[0046] ·Workability During kneading with the 12-inch mixing roll, bagging and sticking were evaluated as follows. The evaluation results are shown in Table 2. Bagging ◎: No bagging occurs ○: Bagging occurs, but can be dealt with by kneading ×: Bagging occurs and kneading is difficult
[0047] Sticking ◎: No sticking occurs ○: Sticking occurs, but it can be dealt with by kneading ×: Sticking occurs and kneading is difficult
[0048] -Surface properties of rubber sheet The unvulcanized rubber sheet obtained in the production of the rubber composition was used to visually observe the surface of an area of 150 mm x 300 mm, and the surface properties of the rubber sheet were evaluated as follows. The evaluation results are shown in Table 2.
[0049] ◎: No X-ray shielding particles can be seen on the surface ○: X-ray shielding particles are present on the surface or there are small holes ×: Holes in the product
[0050] Air failure When the rubber sheet was molded, the surface of the X-ray shielding composition was observed immediately after removal from the mold, and swelling due to poor air intake was evaluated as follows. The evaluation results are shown in Table 2. ◎: No air ○: 1 to 5 air particles present when demolded ×: 6 or more air bubbles present when demolded
[0051] ·Coverage rate The shielding rate [%] is the X-ray shielding rate of the X-ray shielding composition evaluated. The shielding rate was calculated by calculating the linear absorption coefficient [cm-1] of each X-ray shielding composition from the ratio of the X-ray shielding material contained in each X-ray shielding composition evaluated and the volume ratio of the X-ray shielding material, and then calculating the shielding rate for a thickness of 1.5 mm. Note that the linear absorption coefficient at this time was calculated by assuming the X-ray spectrum of a CT device and multiplying each value by a coefficient in the range of 10 to 120 keV, and the sum was used. For reference, the shielding rate of lead calculated by the above-mentioned method is 99.8%.
[0052] (Examples 1 to 18 and Comparative Examples 1 to 3) The same procedure as in Example 1 was carried out, except that the blending amounts (parts by mass) of each material were changed as shown in Table 1. The evaluation results are shown in Table 2. As described above, in Examples 1 to 18, X-ray shielding compositions having good processability while maintaining sufficient shielding performance could be obtained.
[0053] [Table 1]
[0054] [Table 2]
Claims
1. An X-ray shielding composition comprising a rubber material, a first shielding material that is mixed with the rubber material and contains at least one of tungsten and a tungsten compound; A second shielding material is mixed with the rubber material and contains at least one of bismuth and bismuth oxide, a ratio of the X-ray shielding material composed of the first shielding material and the second shielding material to the X-ray shielding composition is 40 vol% or more and 60 vol% or less, A volume ratio of the first shielding material to the second shielding material is within a range of 0.5:9.5 to 8:2; The X-ray shielding composition has an X-ray shielding rate of 93.9% or more at a thickness of 1.5 mm. X-ray shielding composition.
2. The volume ratio of the first shielding material to the second shielding material is within a range of 3:7 to 8:
2. The X-ray shielding composition of claim 1 .
3. The ratio of the rubber material to the X-ray shielding composition is 20% by volume or more and less than 50% by volume. The X-ray shielding composition according to claim 1 or 2.
4. The second shielding material is bismuth oxide. The X-ray shielding composition according to any one of claims 1 to 3.
5. The reinforcing filler is contained in an amount of 0.5% by volume or more and less than 2.0% by volume. The X-ray shielding composition according to any one of claims 1 to 4.
6. The X-ray shielding composition does not contain lanthanum trioxide. The X-ray shielding composition according to any one of claims 1 to 5.
7. A method for producing an X-ray shielding composition comprising a rubber material, a first shielding material containing at least one of tungsten and a tungsten compound, and a second shielding material containing at least one of bismuth and bismuth oxide, comprising: a kneading step of kneading the rubber material, the first shielding material, and the second shielding material with a mixing roll, wherein the ratio of the X-ray shielding material composed of the first shielding material and the second shielding material to the X-ray shielding composition is 40 volume % or more and 60 volume % or less, and the volume ratio of the first shielding material to the second shielding material is within a range of 0.5:9.5 to 8:2; A crosslinking step of crosslinking the composition produced by the kneading, The X-ray shielding composition has an X-ray shielding rate of 93.9% or more at a thickness of 1.5 mm. A method for producing an X-ray shielding composition.
8. The volume ratio of the first shielding material to the second shielding material is within a range of 3:7 to 8:
2. A method for producing the X-ray shielding composition according to claim 7.
9. The ratio of the rubber material to the X-ray shielding composition is 20% by volume or more and less than 50% by volume. A method for producing the X-ray shielding composition according to claim 7 or 8.
10. The second shielding material is bismuth oxide. A method for producing the X-ray shielding composition according to any one of claims 7 to 9.
11. The crosslinking step includes a reinforcing filler in an amount of 0.5% by volume or more and less than 2.0% by volume relative to the X-ray shielding composition. A method for producing the X-ray shielding composition according to any one of claims 7 to 10.
Citation Information
Patent Citations
Irradiation-resistant lead-free radiation-shielding flexible material as well as preparation method and application thereof
CN111849175A
Medical x-ray shield material
JP2001083288A
New radiation-attenuating material and method for manufacturing the same
JP2004531730A
Radiation-attenuating elastomer material, multilayer protective gloves against ionizing radiation, and method of use thereof.
JP2013501084A
Radiation shield material composition and radiation shield material
JP2017173296A